Design a 25-level inverter topology with less switching devices fed by PV systems - Ali Riyadh Ali; Abdulghani Abdulrazzaq Abdulghafoor; Rakan Khalil Antar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Multilevel inverter (MLI) technology has lately emerged as one of the most popular solutions for high power and medium voltage energy management. MLIs have many benefits and require more switches for higher levels, which are considered disadvantaged. This could result in large size and extremely expensive cost for the MLI. So, in order to overcome this problem, a new MLI topology is proposed with reduced number of switches. A 25â€level inverter fed by isolated unequal photovoltaic panels as DC sources is chosen in this study. The structure of DC voltages is chosen as (1:1:5:5) Vdc. The proposed approach, which is created using twelve switches, is ideally suited for a high-power application. Multi-carrier with a sinusoidal PWM technique is programmed as a controller. According to the simulation findings, a single-phase system's output voltage and current total harmonic distortion (THD) values are 1.2% and 0.462%, respectively, while a three-phase system's values are 1.07% and 0.342%. These findings prove that the power circuit and investigation were successful.